THE ROLE OF THE OPERATIONAL COST BUDGET AS A TOOL FOR CONTROLLING MANAGERIAL PERFORMANCE - Mhd.Shafwan Aziz; Henny Andriyani Wirananda; Shita Tiara; Sri Wardany (CV. Barokah Publsiher, 2026)
This study pays attention to the function of the operational cost budget as a tool to control managerial performance at PT Darmasindo , a company operating in the rubber industry sector that produces semi-finished goods in the form of rubber sap, with data obtained from the period 2022 to 2024. In the highly competitive rubber industry and requires efficient cost management, proper budget utilization is essential to achieve efficiency and effectiveness in operations. The research methodology applied is qualitative descriptive analysis, with data collection through interviews with managers and employees, as well as through analysis of budget documents and performance reports. The findings of the study show that PT. Darmasindo has successfully implemented an operational cost budget well, where this budget not only serves as a planning tool but also as a performance benchmark that assists managers in determining strategic decisions. The implementation of the budget shows a positive impact on managerial performance, including increased efficiency in resource utilization, more effective cost control, and increased overall productivity. However, this study also found several challenges faced by PT. Darmasindo, including changes in fuel prices and uncertainty in operations. This challenge requires quick adjustments and adaptations in managing the budget so that performance is maintained properly.